Electrochemical DNA sensor for herpes virus detection - Tâm và cộng sự, Phương Đình (Vietnam Journal of Chemistry, 2014)
This paper reports the development of electrochemical DNA sensor for biomedical application. The micro-sensor was fabricated at Hanoi University of Technology clean room by microelectronic technology. Two pairs of electrodes of which optimized dimension is 70 mm x 30 mm (the width of electrode x inter-distance between fingers), were created on a chip for differential measurements. The DNA of herpes simplex virus 1 (HSV-1) with the DNA probe sequence is 5’–AT CAC CGA CCC GGA GAG GGA C–3’ was immobilized onto the surface of the sensors by means of 3-aminopropyltriethoxysilance (APTS). The results showed that the DNA sensor can determine the DNA target of HSV-1 in the sample at the concentration as low as 0.5 nM. The response time of the DNA sensor is less than a minute. Temperature effect was also investigated in this work. Keywords: DNA sensor, electrochemical detection, APTS, virus, hybridization.